2015
DOI: 10.3390/biom5042935
|View full text |Cite
|
Sign up to set email alerts
|

The RNA Splicing Response to DNA Damage

Abstract: The number of factors known to participate in the DNA damage response (DDR) has expanded considerably in recent years to include splicing and alternative splicing factors. While the binding of splicing proteins and ribonucleoprotein complexes to nascent transcripts prevents genomic instability by deterring the formation of RNA/DNA duplexes, splicing factors are also recruited to, or removed from, sites of DNA damage. The first steps of the DDR promote the post-translational modification of splicing factors to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
136
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(154 citation statements)
references
References 255 publications
(340 reference statements)
12
136
0
Order By: Relevance
“…Recognition of the importance of RBPs for the DDR has increased in recent years (Lenzken et al 2013;Dutertre et al 2014;Naro et al 2015;Shkreta and Chabot 2015;Kai 2016). Using differential quantification of the poly(A) + RNA-protein interactome, we identified more than 260 RBPs that displayed increased binding activity to polyadenylated transcripts upon induction of DSBs in cultured human breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recognition of the importance of RBPs for the DDR has increased in recent years (Lenzken et al 2013;Dutertre et al 2014;Naro et al 2015;Shkreta and Chabot 2015;Kai 2016). Using differential quantification of the poly(A) + RNA-protein interactome, we identified more than 260 RBPs that displayed increased binding activity to polyadenylated transcripts upon induction of DSBs in cultured human breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…On the cellular level, DDR impacts multiple layers of cell fate decisions from activation of specific DNA repair mechanisms, cell cycle progression/arrest, to apoptotic or senescent phenotypes (Zhou and Elledge 2000). Importantly, a significant fraction of these decisions are mediated by a transcriptional response, which is largely under the control of TP53, a transcription factor that regulates expression of cell cycle regulators such as cyclin-dependent inhibitor protein 1A (CDKN1A/p21), apoptotic proteins (e.g., BAX, BBC3/PUMA), and DNA repair components (Riley et al 2008;Shkreta and Chabot 2015).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…DNA damage can alter the gene expression, subcellular localization, and protein modification of splicing factors, which ultimately affect the production of components that control cell fate through splicing [9][10][11][12][13][14]. Previous work has indicated that AS of genes involved in DNA damage response (DDR)-related processes, such as DNA repair, cell cycle control, and apoptosis, are extensively modulated by DNA damage [15]. On the other hand, deficiencies in some splicing factors can also induce DNA damage [16,17], which suggests a close cross-regulation between AS and DNA damage.…”
Section: Introductionmentioning
confidence: 99%